DNA methylation status of interspersed repetitive sequences in patients with migraine - Nino Kraveishvili; Eka Kvaratskhelia; Sandro Surmava; Merab Kvintradze; Maia Zarandia; Tinatin Gorgiladze; Elene Abzianidze (Journal of International Medical Research, 2023)
Objective To analyse the methylation status of the Long Interspersed Nuclear Element-1 (LINE-1) and Short Interspersed Nuclear Element Alu (Alu) of peripheral blood mononuclear cells (PBMCs) from patients with migraine compared with healthy control subjects. Methods This case–control study recruited patients with migraine without aura and age-matched healthy control subjects. PBMCs were purified from peripheral blood samples. Methylation levels and patterns of LINE-1 and Alu sequences were evaluated using combined bisulfite restriction analysis-interspersed repetitive sequences polymerase chain reaction. Results A total of 84 patients with migraine and 82 age-matched healthy controls were enrolled in the study. High levels of unmethylated cytosines in both the LINE-1 and Alu repetitive elements were observed in the migraine group compared with the control subjects. In addition, a significant difference was detected in the methylation level of LINE-1 between TT and CC genotype groups of the methylenetetrahydrofolate reductase gene. Conclusions These results suggest that analysis of epigenetic biomarkers in PBMCs may help to identify patients at a higher risk of migraine development.